Marching toward hell : America and Islam after Iraq - Scheuer, Michael (New York : Free Press, 2008)
CIA veteran Scheuer examines the ongoing instability in Iraq and argues that the U.S has provided al Qaeda and its allies with the one thing they want most: a safe haven from which to launch operations across borders into countries that were previously difficult for them to reach. With U.S. forces and resources spread thinner every day, the war has depleted our strength and brought al Qaeda a kind of success that it could not have achieved on its own. Scheuer takes on the questions of "What went wrong?" and "How can we fix this?" and proposes a plan to cauterize the damage that has already been done and get American strategy back on track. He lists a number of painful recommendations for how we must shift our ideological, military, and political views in order to survive, even if that means disagreeing with Israeli policy or launching more brutal campaigns against terrorists.--From publisher description.
Getting to 9/11 -- Readying bin Laden's way : America and the Muslim world, 1973-1996 -- Fighting Islamists with a blinding Cold War hangover, 1996-2001 -- Six years of war, 2001-2007 -- Afghanistan : a final chance to learn history applies to America -- Iraq : America bled white by history unlearned -- And the Islamists' fire quietly spreads -- Where stands the war? -- "The bottom is out of the tub" : taking stock for America in 2008 -- "O enemy of God, I will give Thee no respite" : al-Qaeda and its allies take stock -- Where to from here? -- A humble suggestion : America first -- Epilogue : an abiding uniqueness.
Includes bibliographical references (p. 329-346) and index.
Keywords: Afghan War, 2001-; Iraq War, 2003-2011.; Islam -- 21st century; Islamic countries -- Foreign relations -- Iraq; United States -- Politics and government -- 2001-2009.